PENDIDIKAN MODERASI BERAGAMA DI ERA TEKNOLOGI - Elsina Sihombing; Yohana Nelly Panjaitan; Humiras Pakpahan; Nova Yanti Rumapea; Wasti Sitanggang; Desi Kristina Manalu (STKIP Subang, 2026)
The development of digital technology has brought significant changes to people's lives, including in the fields of education and religious life. On the one hand, technology provides convenience in accessing information and supports the learning process, but on the other hand, it also creates challenges such as the spread of hoaxes, intolerance, hate speech, and radicalism through digital media. Therefore, religious moderation education is important in shaping tolerant, wise, and responsible attitudes in the use of technology. This study aims to examine the importance of religious moderation education in the technological era and the role of education in developing students’ character so that they are able to live harmoniously within a diverse society. This research uses a library research method with a qualitative descriptive approach through the study of various books, journals, and relevant scientific sources. The results show that religious moderation education has a strategic role in instilling the values of tolerance, balance, respect for diversity, and digital literacy skills among students. Education integrated with religious moderation and digital literacy can help students face the negative impacts of technological development and create peaceful and harmonious social life. Therefore, cooperation among schools, teachers, families, and communities is needed to support the implementation of religious moderation education in the technological era